Relationship between reproductive and creative components in the activities of musician and choreographer as leaders of folklore centers (Pedagogy of Higher and Secondary Education, 2009)
In this article, the interaction of art language in the creative work of musician: and dancers as leaden of the folklore structures different in the form of expression and ways of activity is considered.
Keywords: musician; choreographic; interaction of arts; folk creation; activity